Global Existence and Blow-up for a Two-Dimensional Attraction-Repulsion Chemotaxis System (Communications in Mathematical Research, 2019)
This paper is devoted to dealing with the parabolic-elliptic-elliptic attraction-repulsion chemotaxis system. We aim to understand the competition among the repulsion, the attraction, the nonlinear productions and give conditions of global existence and blow-up for the two-dimensional attraction-repulsion chemotaxis system.
Keywords: chemotaxis; attraction-repulsion; global boundedness; nonradial solution; blow-up.